Ṿeshe-Einan nirʾot: feminizm ḥaredi : ha-miḳreh shel "lo nivḥerot lo boḥrot" = Invisible women : Ultra-Orthodox feminism: the case of "no voice no vote" campaign - Rieder-Indursḳi, Esti (Pardes, 2018)
Ultra-Orthodox feminism: the case of "no voice no vote" campaign